Gradient-based LASER Land Leveling Increases the Water Use Efficiency, Growth, and Yield of Cotton Crop under Changing Climate: Gradient-based laser land leveling - Shahid Saleem,; Iqbal Hussain,; Hafeez Ullah,; Muhammad Umar Iqbal,; Umair Aslam,; Muhammad Nasir,; , Abdul Khaliq,; Syed Ahtisham Masood,; Hafiz Abdul Rauf,; Adnan Noor Shah,; Fida Hussain, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Increasing water shortage has compelled farmers to develop plans for efficient use of water resources. The improvement in water use efficiency at the field level is very important and can redress water scarcity. LASER land leveling is increasing quickly in the world to increase water use efficiency. However, in developing countries, the practice of LASER leveling is to level land or field with zero (0 %) gradient due to unawareness of gradient-based land leveling while a small gradient (e.g., 0.1 %) is usually kept during land leveling in developed countries of the world. But farmers of developing countries are not well, therefore, an experiment was conducted in farmers’ fields covering an area of 3 acres in south Punjab of Pakistan to assess the LASER leveling with a 0 % and 0.05 % grade and general farmer’s practice of leveling. Land leveling with LASER using a 0.05 % gradient considerably decreased the amount of irrigation water and/or enhanced water use efficiency by increasing crop yield followed by LASER leveling with a 0 % gradient. Similarly, with a 0.05 % gradient, bolls per plant and final cotton yield increased considerably followed by a 0 % gradient while minimum bolls per plant and cotton yield were obtained from the farmer’s practice of leveling. LASER land leveling with a 0.05 % gradient resulted in higher net benefit due to increased yield and a considerable decrease in irrigation amount that significantly improved use efficiency. The outcomes suggest that benefits from land leveling with LASER keeping a 0.05 % gradient are significantly higher when compared with 0 % gradient and/or farmers’ practice of leveling.